2020
DOI: 10.2174/1872210513666190702165556
|View full text |Cite
|
Sign up to set email alerts
|

Study of 5-Fluorouracil Loaded Chitosan Nanoparticles for Treatment of Skin Cancer

Abstract: Background: The purpose of this study was to formulate, characterize and in-vitro cytotoxicity of 5-Fluorouracil loaded controlled release nanoparticles for the treatment of skin cancer. The patents on nanoparticles (US8414926B1), (US61654404A), (WO2007150075A3) etc helped in the selection polymers and method for the preparation of nanoparticles. Methods: In the present study nanoparticles were prepared by simple ionic gelation method using various concentrations of chitosan and sodium tripolyphosphate. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Chitosan ---------5-Fluorouracil Skin cancer Provided improved inhibitory effect on cancer cell lines than drug solutions. [115] Folic acid-coated CSNPs MW = 310,000-375,000, DD = 83% 5-Fluorouracil Colon cancer Provided improved cytotoxicity of the NPs on coating with folic acid than uncoated CSNPs. [27] Chitosan -------------Chlorambucil Breast cancer…”
Section: Chitosan Nanoparticles As Anticancer Drug Delivery Systemmentioning
confidence: 99%
“…Chitosan ---------5-Fluorouracil Skin cancer Provided improved inhibitory effect on cancer cell lines than drug solutions. [115] Folic acid-coated CSNPs MW = 310,000-375,000, DD = 83% 5-Fluorouracil Colon cancer Provided improved cytotoxicity of the NPs on coating with folic acid than uncoated CSNPs. [27] Chitosan -------------Chlorambucil Breast cancer…”
Section: Chitosan Nanoparticles As Anticancer Drug Delivery Systemmentioning
confidence: 99%
“…As per Patel Gayatri et al (2020), by ionic gelation method and in the presence of chitosan and sodium tripolyphosphate (TPP), 5-Fluorouracil loaded nanoparticles were prepared. The cytotoxicity studies were carried out by MTT assay using A375 basal cell carcinoma cell-line (15). For topical drug delivery, the solid lipid nanoparticles approach would be the best possible solution to treat metastatic malignant melanoma (16,17).The prepared solid lipid nanoparticles can be stabilized by using suitable surfactant and co-surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Several studies in the field of 5-FU-loaded polymer NPs can be found in the literature. 28,[34][35][36] For example, Rahmani and coworkers 37 prepared silk fibroin NPs containing 5-FU as a reliable drug delivery system for cancer treatment with high loading capacity and sustained release profile.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Several studies in the field of 5-FU-loaded polymer NPs can be found in the literature. 28,34–36 For example, Rahmani and coworkers 37 prepared silk fibroin NPs containing 5-FU as a reliable drug delivery system for cancer treatment with high loading capacity and sustained release profile. Their results displayed that by increasing the amount of drug, a deformation occurred in the structure of the NPs, which reduced the particle size, increased the loading efficiency and revealed slower and more controlled release.…”
Section: Introductionmentioning
confidence: 99%